Critical Success Factors in the Implementation of Quality Systems in the Distribution Sector of the Oil Industry in Malaysia - Omar, Mohd Yusof (1998)
The distribution sector of the oil industry in Malaysia, encompassing a sample of nine distribution worksites, was studied to investigate what the Critical Success Factors (CSFs) in the implementation of quality systems to ISO 9000 were. The data sought would be the C SFs and the leadership qualities that consistently determine the success of the implementation. One hundred and nine-three staff at nine locations were observed. The study was carried out in two phases. The first phase was spent identifying the CSFs in the implementation of quality systems through readings and observation. The second phase was spent validating and testing the reliability of the hypothesis at eight distribution worksites. Results of the baseline assessment were statistically analysed utilising the SAS software. Descriptive statistics were derived from the observed data. The multivariate statistical procedures of principal component analysis (PCA) and factor analysis were adopted. Through the PCA the identified seventeen leadership qualities [adapted from Jameson and Soule ('91 )] were reduced to twelve. They were: ability to organise, resolution of complaints, leadership among peers, helpfulness, written ability, open-mindedness, respect/consideration for others, diplomacy and tact, situation handling, positive influence on others, respect from co-workers and dealing with issues. The PCA also reduced the ten identified CSFs to five. They were: sense of urgency, sense of co-operation, team work, cohesiveness and participation consciousness. Only factors with positive eigenvalues were considered because that would explain one hundred percent of the total variance in the data. To recapitulate, the hypothesis for the research is that the successful implementation of quality systems is a function of the degree of existence of these CSFs and of the leadership qualities of the worksite managers. The CSFs and leadership qualities were, therefore, valid because certification was awarded to each distribution worksite each time identified gaps from the baseline assessments at each site (against the CSFs and leadership qualities) were remedied.